Elucidating the molecular mechanisms underlying cellular response to biophysical cues using synthetic biology approaches. Issue 5 (2nd September 2016) - Denning, Denise; Roos, Wouter H.
ABSTRACT: The use of synthetic surfaces and materials to influence and study cell behavior has vastly progressed our understanding of the underlying molecular mechanisms involved in cellular response to physicochemical and biophysical cues. Reconstituting cytoskeletal proteins and interfacing them with a defined microenvironment has also garnered deep insight into the engineering mechanisms existing within the cell. This review presents recent experimental findings on the influence of several parameters of the extracellular environment on cell behavior and fate, such as substrate topography, stiffness, chemistry and charge. In addition, the use of synthetic environments to measure physical properties of the reconstituted cytoskeleton and their interaction with intracellular proteins such as molecular motors is discussed, which is relevant for understanding cell migration, division and structural integrity, as well as intracellular transport. Insight is provided regarding the next steps to be taken in this interdisciplinary field, in order to achieve the global aim of artificially directing cellular response.